Penang Goes Orange 2024 @ UiTM: a united stand against online gender-based violence / Noor Azli Affendy Lee, Nazima Versay Kudus and Ts. Dr. Adi Izhar Che Ani - Affendy Lee, Noor Azli; Versay Kudus, Nazima; Che Ani, Adi Izhar (Academy of Language Studies, 2025)
On 7 December 2024, the Penang Goes Orange 2024 (PGO2024) campaign was held at Dewan Besar, Universiti Teknologi MARA Penang Branch (UiTMCPP). Permatang Pauh Campus, marking a significant milestone in the 11-year history of this initiative by the Penang Women’s Development Corporation (PWDC). dedicated to combating gender-based violence. Under the theme #Swipe2Stop. this year’s campaign focuses on addressing online sexual harassment, particularly among youth, through advocacy, awareness, and action.